SOCIETY OF KNOWLEDGES AS SPACE OF DEVELOPMENT OF INTELLECT OF PERSONALITY - G. Moskalyk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. In the article the author analyzes the history of the formation of the concept of "knowledge society", stressed the ambiguity of the category "knowledge". We consider the views of various researchers on topics studied question, their difference and contradiction, analyzed the degree of research scholars of the subject. The author of the article pays attention to the integrity and consistency – logical properties of the educational process. The concept of "resources", "intellectual resources". Proven strategic resources of building a "knowledge society" are creativity and intellectual development. Methodology. The author in the publication examines the concept of intelligence, its nature from the perspective of the intellect of the person. Reviewed and defined the essence of the new paradigm of education – "Education throughout life", and the element of the new educational paradigm is the concept of fundamentalization of education. The scientific novelty. The analysis of the conceptual apparatus, the formation of a new educational paradigm. Conclusions. After consideration of all factors and reasons, the author concludes that the scope for the functioning and deployment of intelligence of the individual is the knowledge society.